Pergeseran Nilai Perayaan Hinamatsuri Di Jepang Dewasa Ini - Ni Komang Nanik Purnami; Ni Wayan Meidariani (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2024)
Hinamatsuri is a Japanese festival held every 3rd of March to pray for the health and happiness of girls. Japanese people celebrate Hinamatsuri by throwing paper dolls into the river, but with the development of the times and the influx of outside cultures, Hinamatsuri(ひな祭り) festivities take place with great fanfare today. The purpose of this study is to describe and analyze the shifting values of the Hinamatsuri(ひな祭り) festival in Japan. The theory used in this research is social change according to Piotr Sztompka. The method used by the author is library research method and field study by sending questionnaires to 30 Japanese women as supporting data. The results show that there are two causes that make the shift in the value of the Hinamatsuri festival (ひな祭り), namely: 1. The revolution of the times, 2. The situation and condition of Japanese women